Fabrication and optical characterization of Bragg resonance luminescence porous silicon. (1st October 2015) - Park, Mi-Ae; Sohn, Honglae
Abstract: The synthesis and characterization of Bragg resonance luminescence porous silicon (BRL PS) exhibiting both optical reflectivity and strong narrow visible photoluminescence (PL) prepared from highly doped n-type silicon wafers through the electrochemical etching are reported. BRL PS showing the luminescence at 702 nm with an excitation wavelength of 400 nm was prepared by applying the current of 360 mA cm −2 for 1.6 s and 75 mA cm −2 for 3.6 s with 50 repeats in etching solution of 1:1 volume mixture of absolute ethanol and aqueous 48% HF. BRL PS exhibited sharp PL peak which reached full width at half maximum of 14 nm, originated from the result of Bragg resonance in PS multilayer. The sharp PL peak at 702 nm of BRL PS is the second-order transmitted luminescence peak by Bragg resonance phenomenon. The simultaneous measurement of reflectivity and luminescence in the BRL PS under an exposure to a vapor flux of acetone showed that a narrow transmitted luminescence based on Bragg resonance in BRL PS quenched as well as the red-shifted by 37 nm of reflection wavelength was observed. A dramatic quenching PL of BRL PS compare to that of the monolayer PS, is probably due to the Bragg resonance effect on luminescence.